Social Media Used in Higher Education: A Literature Review of Theoretical Models - Al-Rahmi, Waleed Mugahed; Alias, Norma; Shahizan, Mohd (International Series on Interdisciplinary Science and Technology, 2016)
Abstract— This research provides a literature review related with social media used for collaborative learning and engagement in turn, to affect students' academic performance in higher education. Therefore, the main objective of this research is to review models on social media use for active collaborative learning and engagement by interactive and perceptual factors in turn affecting the learning performance of research students. Therefore, this study conducted on two theories constructivism theory and Technology Acceptance Model (TAM). This paper conducted an analysis of studies dedicated to social media use for collaborative learning and engagement based on previous research problems of models, and the theories. According to the literature review and discussion in this research, we noted the full satisfaction of students was through the use of social media for active collaborative learning and engagement to positively affect their learning performance. Keywords— Social Media, Collaborative Learning, Students’ Academic Performance, Theoretical Model